2014
DOI: 10.1124/mol.114.093302
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Transporter Inhibition with Desipramine Exacerbates L-DOPA–Induced Dyskinesia: Role for Synaptic Dopamine Regulation in Denervated Nigrostriatal Terminals

Abstract: Pharmacological dopamine (DA) replacement with Levodopa [L-dihydroxyphenylalanine (L-DOPA)] is the gold standard treatment of Parkinson's disease (PD). However, long-term L-DOPA treatment is complicated by eventual debilitating abnormal involuntary movements termed L-DOPA-induced dyskinesia (LID), a clinically significant obstacle for the majority of patients who rely on L-DOPA to alleviate PD-related motor symptoms. The manifestation of LID may in part be driven by excessive extracellular DA derived from L-DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 84 publications
0
26
1
Order By: Relevance
“…Acute systemic administration of desipramine (25 mg/kg), a selective NET inhibitor, increases the extracellular dopamine concentration after levodopa treatment in the striatum of this PD model (Arai et al, 2008). Chronic administration of desipramine (12 mg/kg) also increases the striatal dopamine concentration and enhances dyskinesia-like behaviors induced by levodopa injection to this model rat (Chotibut et al, 2014). These studies suggest that NET has a significant role in reuptake of extracellular dopamine in the PD striatum.…”
Section: The Role Of Norepinephrine Transporters In Reuptake Of Dopammentioning
confidence: 96%
See 1 more Smart Citation
“…Acute systemic administration of desipramine (25 mg/kg), a selective NET inhibitor, increases the extracellular dopamine concentration after levodopa treatment in the striatum of this PD model (Arai et al, 2008). Chronic administration of desipramine (12 mg/kg) also increases the striatal dopamine concentration and enhances dyskinesia-like behaviors induced by levodopa injection to this model rat (Chotibut et al, 2014). These studies suggest that NET has a significant role in reuptake of extracellular dopamine in the PD striatum.…”
Section: The Role Of Norepinephrine Transporters In Reuptake Of Dopammentioning
confidence: 96%
“…They discussed that the contradictory result of Arai et al (2008) is because of their high dose of desipramine (25 mg/kg), in which desipramine non-selectively binds to sites other than NET. However, Chotibut et al (2014) used a lower dose of desipramine (12 mg/kg) and demonstrated a significant increase of levodopa-derived dopamine concentration in the dopamine-denervated striatum. The inconsistencies between studies may be due to residual DAT expression and activity of SERT and other monoamine transporters in the particular experimental situation (Figure 2B).…”
Section: The Role Of Norepinephrine Transporters In Reuptake Of Dopammentioning
confidence: 99%
“…Indeed, blockade of the noradrenergic transporter by desipramine administration has been recently shown to produce the opposite effect on LID in rats, i.e. worsening of the dyskinesia score (Chotibut et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…LC NE neurons terminating in the striatum may influence striatal DA levels by modifying DA uptake. Indeed, evidence shows that striatal NE transporters (NET) can take up L-DOPA-derived DA in the DA-depleted brain [72] and subsequent NET blockade exacerbated LID expression in a rodent model of LID [73]. NE from the LC could also modulate striatal DA signaling indirectly by regulating striatal DA release from the SNc [74, 75].…”
Section: Discussionmentioning
confidence: 99%